Deciphering Mineralogical Composition and Clay Diagenesis in Exposed Shales of Jaintiapur, Surma Basin: Unveiling Insights into Burial Diagenesis - Joy, Md Fazle Rabbi; Bhuiyan, Md Anwar Hossain; Rahman, Md Mostafizur (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Mineralogical analysis of exposed shale samples in the Jaintiapur region was conducted utilizing X-ray diffraction (XRD) techniques. The studied shales are characterized by illite, chlorite, illite/ smectite mixed layer clay, and kaolinite as the predominant clay minerals, with a relatively lower proportion of smectite. Additionally, the non-clay fraction consists mainly of quartz, feldspar, dolomite, and trace amounts of pyrite. Notably, illite and chlorite exhibit prominent abundance within the clay portion, while quartz is the prevailing non-clay mineral. Furthermore, the investigation reveals a notable enrichment of illite and chlorite with the advancement from younger to older stratigraphic formations in the studied shale samples, indicating greater intensity in clay mineral diagenesis in deeper stratigraphic formations. The transition from smectite to illite minerals can release Si, Ca, Fe, and Mg ions, potentially entering nearby sandstones and leading to cementation with quartz, chlorite, and calcite. This process aids in retaining pore water in shales. In this context, overpressure development influenced by clay diagenesis is not primarily due to cementation while undergoing smectite to illite conversion but due to illite packet formation within smectite, reducing shale permeability. During this conversion, interlayer water shifts to free water, causing volume reduction compounded by the low permeability of shale, trapping fluids in the pores. This expansion of pore water, reduced velocity, and increased pore pressure suggest that mineral transformation with burial depth might contribute to overpressure development. However, the observed decline in smectite clays in sediments transitioning from younger to older, culminating in their absence in older shale-dominated formations, explains the presence of diagenetic illite and chlorite. This study underscores the progressive diagenetic transformation in clay mineralogical composition with progressive burial across the sedimentary succession. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 69-82